Some geometric properties of generalized difference Cesàro sequence spaces - Şengül, Hacer; Et, Mikail (Chiang Mai University, 2017)
In this paper, we define the generalized Cesàro difference sequence space C(p) (?m) and consider it equipped with the Luxemburg normunder which it is a Banach space and we show that in the space C(p) (?m) every weakly convergent sequence on the unit sphere converges is the norm, where p = (pn) is a bounded sequence of positive real numbers with pn > 1 for all n ? N. © 2017 by the Mathematical Association of Thailand. All rights reserved.
Keywords: Cesàro difference sequence space; Convex modular; Extreme point; Luxemburg norm; Property (H)